Some notes on port-Hamiltonian systems on Banach spaces. Issue 19 (2021) - Reis, Timo
Abstract: We consider port-Hamiltonian systems from a functional analytic perspective. Dirac structures and Hamiltonians on Banach spaces are introduced, and an energy balance is proven. Further, we consider port-Hamiltonian systems on Banach manifolds, and we present some physical examples that fit into the presented theory.